Design and Development of Mobile Application: Nursery.com Application - Nurul Ain Najwa Ghazali,; Sharmila Mat Yusof, (Multidisciplinary Applied Research and Innovation, 2023)
The ever-increasing use of the internet in Malaysia presents a rising opportunity for e- marketers. In the field of Horticulture, an electronic commerce website or application consist of buying and selling products. The e-commerce website is very helpful for customers and gardeners even though selling plants and gardening products online is not as widespread as selling books or new high-tech gadgets. However, problems are still existed where most of the gardeners or nursery owner still experiencing difficulties in selling their product and reaching more customers. Besides, customers are also facing difficulties in comparing the price of the plants and gardening products from various nurseries. The Nursery.com applications intend to assist local gardeners in selling their plants online and to offer customers a more practical and trustworthy means to search, compare, and purchase the desired plants that are suited for their needs. Customers can also access product descriptions and details online and search the various of nursery shop. Additionally, a door-step delivery was also offered for customer. An agile methodology was adopted to develop this application. The methodology was chosen because it allows for modifications in requirements at any time. While working on the development, the developer can listen to end-user feedback to meet the end requirements of users. Finally, the foresee advantage of the application is that it can help nursery owners to market their product in a wider area coverage. In addition, customers can have more options and good deals from the various nursery stores at a single platform.